DETERMINANTS OF VEGETABLE LOSS AND WASTE ALONG MARKETING CHANNELS IN PLATEAU STATE, NIGERIA: EVIDENCE FROM A MULTIPLE REGRESSION MODEL - Margwa, R.S.; Jibril, S.A.; Mohammed, I.; Shehu, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
This study employed multiple regression analysis to determine the causes of vegetable loss and waste among 360 marketers across 16 vegetable markets in nine Local Government Areas of Plateau State, Nigeria, during the 2022 cropping season. Five predictor variables were modelled: mode of transportation, distance to market, storage system quality, marketing experience, and vegetable shelf life. The model explained 69.6% of the total variation in vegetable loss (R² = 0.696; F = 12,055.51; p < 0.001). All five variables were statistically significant (p < 0.001), with marketing experience as the largest contributor (β = −0.265; 26.5% contribution), followed by transportation (β = −0.260; 26.0%), shelf life (β = −0.148; 20.2%), storage system (β = −0.158; 15.8%), and distance to market (β = 0.081; 8.1%). Collectively, these factors account for 69.6% of all vegetable losses in the Plateau State marketing system. The findings provide a nuanced, evidence-based framework for targeting post-harvest loss reduction investments, prioritising interventions that address marketers’ experience and training, transportation infrastructure, vegetable shelf-life extension, storage improvement, and market accessibility.